Evidence of a 50-year increase in tropospheric ozone in Upper Bavaria - M. Schmidt (Annales Geophysicae)
In a series of ozone-sonde soundings at the Hohenpeißenberg observatory, starting in 1967, the most striking features are increases of sim2.2% per year in all tropospheric heights up to 8 km during the past 24 years. These facts have recently been published and discussed by several authors. In this paper, we present some evidence for the increase of tropospheric ozone concentrations during the past 50 years 1940-1990 in the territory of the northern edge of the Bavarian Alps, including the Hohenpeißenberg data. In December 1940 and August 1942, probably the first exact wet-chemical vertical soundings of ozone up to 9 km height were made by an aircraft in the region mentioned. These results were published in the earlier literature. We have converted the results of the flights on 4 days in December 1940 and on 6 days in August 1942 to modern units and have compared them with the Hohenpeißenberg ozone-sonde data of the December and August months. We also compared the data at the ground with the August results of Paris-Montsouris 1886-1898. Our results show an increase of ozone concentration at all tropospheric heights in Upper Bavaria during the past 50 years, compared with the Montsouris data in August during the past 105 years. In the recently published papers, the increases since 1967 were approximated linearly.Our results, extended to the past, show non-linear trends, with steeper increases since 1975-1979. Possible reasons for these findings are discussed. Quite recently (in case of the December months since 1986/87, the August months since 1990), the ozone mixing ratios at and above Hohenpeißenberg seem to have decreased.